2015
DOI: 10.1371/journal.pone.0123189
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylation in Cell Wall Proteins in Scedosporium prolificans Is Critical for Phagocytosis and Inflammatory Cytokines Production by Macrophages

Abstract: In this study, we analyze the importance of O-linked oligosaccharides present in peptidorhamnomannan (PRM) from the cell wall of the fungus Scedosporium prolificans for recognition and phagocytosis of conidia by macrophages. Adding PRM led to a dose-dependent inhibition of conidia phagocytosis, whereas de-O-glycosylated PRM did not show any effect. PRM induced the release of macrophage-derived antimicrobial compounds. However, O-linked oligosaccharides do not appear to be required for such induction. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 46 publications
1
37
1
Order By: Relevance
“… 9 The filamentous fungus L. prolificans (formerly Scedosporium prolificans ) can interact with peritoneal macrophages, and its surface PRM also participates in this crucial event. 23 Similarly, in A. fumigatus , it was reported that a small number of conidia were internalised and that most of them remained adhered to the external surface of the A549 cells. Those adhered conidia could externally germinate, generating long hyphae after 24 h of fungi-host cell contact.…”
Section: Resultsmentioning
confidence: 95%
“… 9 The filamentous fungus L. prolificans (formerly Scedosporium prolificans ) can interact with peritoneal macrophages, and its surface PRM also participates in this crucial event. 23 Similarly, in A. fumigatus , it was reported that a small number of conidia were internalised and that most of them remained adhered to the external surface of the A549 cells. Those adhered conidia could externally germinate, generating long hyphae after 24 h of fungi-host cell contact.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, those authors described that after 2 h of coculturing of S. boydii and HEp2 cells, the conidia started to germinate and, subsequently, to penetrate into the plasma membrane of epithelial cells [11]. The PRMs also mediate the in vitro adhesion between L. prolificans conidia and mouse peritoneal macrophages [16]. The conidial adhesion followed by its germination was also observed during the in vitro interaction events of S. apiospermum, S. boydii, and S. aurantiacum with lung epithelial cells (A549), lung fibroblasts (MRC-5), and mouse macrophages (RAW 264.7 line) [7,14,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…For filamentous fungi, some features are well known for the establishment of a successfully infectious process, such as cell wall composition, conidial germination, and secretion of metabolites and hydrolytic enzymes [8,9]. Some of those fungal structures have been studied on Scedosporium/Lomentospora species, such as (i) surface molecules (e.g., peptidorhamnomannans, glucosylceramides, and α-glucan) capable of interacting with host receptors as well as modulating the host immunity responses, (ii) proteases able to cleave key host proteins, including antimicrobial peptides, extracellular matrix proteins, and humoral immune components, (iii) high capacity of conidia to germinate under diverse environmental conditions, and (iv) biofilm formation on a variety of abiotic surfaces and also over mammalian cells [7,8,[10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of fungal molecules that could influence bacterial growth, the present work studied peptidorhamnomannans (PRMs), glycoconjugates commonly exposed on Scedosporium and Lomentospora cell wall that play important roles in cell adhesion and interaction with host immune system, leading to the release of inflammatory cytokines by phagocytic cells (Lopes et al, 2011). PRMs have been already described and characterized in Scedosporium boydii, Scedosporium apiospermum, and Lomentospora prolificans (Pinto et al, 2001;Lopes et al, 2010;Xisto et al, 2015), as well as in Scedosporium aurantiacum (de Meirelles et al, 2020). The PRMs of these four species possess similar epitopes as well as distinct species-specific oligosaccharide chains.…”
Section: Introductionmentioning
confidence: 99%